Thermohydraulic investigation of turbulent flow through a round tube equipped with twisted tapes consisting of centre wings and alternate-axes - Eiamsa-ard, S.; Wongcharee, K.; Eiamsa-ard, P.; Thianpong, C. (My University, 2010)
The effects of the twisted tapes consisting of centre wings and alternate-axes (WT-A) on thermohydraulic properties in a round tube, were investigated. The effects of other three types of twisted tapes including: (1) the twisted tape with wings alone (WT), (2) the twisted tape with alternate axes alone (T-A), and (3) the typical twisted tape (TT), were also studied for comparison. All twisted tapes used were twisted at constant twist length (y) of 57. mm, corresponding to a constant twist ratio (y/. W) of 3.0. The wings were generated along the centre line of the tape with three different angles of attack, (β= 43°, 53° and 74°). Test runs were conducted using water as a testing fluid with Reynolds number range between 5200 and 22,000. Under the similar condition, the heat transfer rate in the tube fitted with the WT-A was consistently higher than those in the tube equipped the WT, T-A and plain tube. It is also found that the heat transfer rate increased with increasing angle of attack. Over the range studied, the use of WT-A at β= 74° was found to be the most effective for heat transfer enhancement, giving thermal performance factor of up to 1.4. Mean values of Nusselt number (Nu), friction factor (f), thermal performance factor (η) provided by the WT-A (at β= 74°) were respectively, 17.7%, 30.6% and 7.8% higher than those in the tube with WT (at β= 74°), 20.8%, 53% and 4.9% higher than those in the tube with T-A, and 62%, 123% and 24% higher than those in the tube with TT. The superior performance of the WT-A over those of the other tapes could be attributed to the combined effects of the following actions: (1) a common swirling flow by the twisted tape (2) a vortex generated by the wing (3) a strong collision of the recombined streams behind each alternate point. For a better understanding on flow phenomena, flow-visualization by smoke wire technique is also presented. In addition, the experimental correlations of Nusselt number, friction factor and thermal performance factor were also developed. © 2010 Elsevier Inc.
Keywords: Alternate axis; Enhanced heat transfer; Swirl flow; Twisted tape; Vortex; Wing